"Bucks without Hair" and "Bullet Points": Social and meta-commentary in Justin Cartwright's In Every Face I Meet. (March 2014) - Graham, Lucy Valerie; Buchanan, Andrea
This article aims to open academic debate about Justin Cartwright's fiction set in England by examining the first of Cartwright's major novels about England, namely In Every Face I Meet (1995). Although South African-born Cartwright has lived in London for more than 40 years, the majority of his novels, about England and Englishness, have received little previous academic attention. We claim that In Every Face I Meet offers social commentary in the form of a subtle, humane critique of English society and culture. Tracing the novel's intertextual allusions, not only to the work of William Blake, but also to a text by the notoriously racist South African writer, Sarah Gertrude Millin, we examine the ways in which In Every Face I Meet explores the interface between metropole and former colony. We conclude by discussing the relevance of Cartwright's interest in the ideas of the social philosopher Isaiah Berlin to reading the novel as meta-commentary, and the tension between reading the novel as social commentary and reading it as metafiction.